The voluntary hypoventilation at low lung volume (VHL) method - Woorons, X. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
The live low train high (LLTH) approach, when applied in certain conditions, seems beneficial for improving performance at sea level. Nonetheless, it is problematic to implement for many athletes due to difficulties in accessing sufficiently high (>2,500 m) in many countries. Furthermore, devices used to simulate altitude (hypoxic tents and chambers, apparatus for breathing O2-depleted air) remain expensive and have practical drawbacks, as they do not allow athletes train in the field. Since the mid-2000s, the numerous studies (around 20 to date) have shown that it is possible to simulate hypoxic training conditions without being at altitude and without using devices to create a hypoxic environment. This can be achieved through voluntary hypoventilation at low lung volume (VHL). The VHL technique involves repeating short periods of end-expiratory breath holding (EEBH) during exercise. This "exhale-hold" technique significantly reduces O2 concentrations throughout the body and therefore creates a state of hypoxia.